X-x(3x-5)=x-2(x(x)+x)-x(x)-14

Simple and best practice solution for X-x(3x-5)=x-2(x(x)+x)-x(x)-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-x(3x-5)=x-2(x(x)+x)-x(x)-14 equation:


Simplifying
X + -1x(3x + -5) = x + -2(x(x) + x) + -1x(x) + -14

Reorder the terms:
X + -1x(-5 + 3x) = x + -2(x(x) + x) + -1x(x) + -14
X + (-5 * -1x + 3x * -1x) = x + -2(x(x) + x) + -1x(x) + -14
X + (5x + -3x2) = x + -2(x(x) + x) + -1x(x) + -14

Multiply x * x
X + 5x + -3x2 = x + -2(x2 + x) + -1x(x) + -14

Reorder the terms:
X + 5x + -3x2 = x + -2(x + x2) + -1x(x) + -14
X + 5x + -3x2 = x + (x * -2 + x2 * -2) + -1x(x) + -14
X + 5x + -3x2 = x + (-2x + -2x2) + -1x(x) + -14

Multiply x * x
X + 5x + -3x2 = x + -2x + -2x2 + -1x2 + -14

Reorder the terms:
X + 5x + -3x2 = -14 + x + -2x + -2x2 + -1x2

Combine like terms: x + -2x = -1x
X + 5x + -3x2 = -14 + -1x + -2x2 + -1x2

Combine like terms: -2x2 + -1x2 = -3x2
X + 5x + -3x2 = -14 + -1x + -3x2

Add '3x2' to each side of the equation.
X + 5x + -3x2 + 3x2 = -14 + -1x + -3x2 + 3x2

Combine like terms: -3x2 + 3x2 = 0
X + 5x + 0 = -14 + -1x + -3x2 + 3x2
X + 5x = -14 + -1x + -3x2 + 3x2

Combine like terms: -3x2 + 3x2 = 0
X + 5x = -14 + -1x + 0
X + 5x = -14 + -1x

Solving
X + 5x = -14 + -1x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-5x' to each side of the equation.
X + 5x + -5x = -14 + -1x + -5x

Combine like terms: 5x + -5x = 0
X + 0 = -14 + -1x + -5x
X = -14 + -1x + -5x

Combine like terms: -1x + -5x = -6x
X = -14 + -6x

Simplifying
X = -14 + -6x

See similar equations:

| S=2(3.14)rh+(3.14) | | y=14-2y | | -6-3=9r-6 | | 0.10(x+10)+0.70x=17 | | 4(2x-5)=3x+13 | | 10P+8=5P-2 | | 13-22=-3x | | 16-3b=0 | | 5=7Y-5Y-3 | | y^2+13y+12= | | 16-36=0 | | 10B-11B=0 | | 2(-4+p)=-8.2+1.8p | | -4=-9+8-29 | | x^2+47x+56=0 | | H(x)=2x^3+5x^2-31x-15 | | -15n^2+13=-10n^2-6n | | 6x(3x-4)(2x+5)= | | x^6-243=0 | | -4=9+8-29 | | 3n^2=-8 | | 51a-56=44 | | 4=9+8-29 | | 10v^7+26v^6+12v^5= | | (m-5)x^2-(m+2)x+(m-1)=0 | | -3(3s-3)-9=-2(8s+2)-2 | | -x+5=29 | | 5x^3+3x^2-10x-6= | | -8x+12=-4x+32 | | 4n=17n+25 | | Y=24-3 | | 3r^2=-7 |

Equations solver categories